Investigating Mazon Creek fossil plants using computed tomography and microphotography - Herrera, Fabiany; Hotton, Carol L.; Smith, Selena Y.; Lopera, Paula A.; Neander, April I.; Wittry, Jack; Zheng, Yuke; Heck, Philipp R.; Crane, Peter R.; D’Antonio, Michael P. (Frontiers in Earth Science, 2023)
More than 20,000 siderite concretions from the Mazon Creek area of northern Illinois, USA are housed in the paleobotanical collections of the Field Museum. A large proportion contain fossil plants of Middle Pennsylvanian age that often have excellent three-dimensional morphology and sometimes anatomical detail. Approximately eighty plant taxa have been recognized from the Mazon Creek Lagerstätte, but few have been studied in detail, and in some cases the systematic affinities of these fossils need reevaluation. The three-dimensional (3D) preservation of Mazon Creek fossil plants makes them ideal candidates for study using x-ray micro-computed tomography (CT), and here we apply these techniques to more accurately reconstruct the morphology of specimens of Tetraphyllostrobus Gao et Zodrow and Crossotheca Zeiller. The mineralogical composition of the fossil plant preservation was studied using elemental maps and Raman spectroscopy. In-situ spores were studied with differential interference contrast, Airyscan confocal super-resolution microscopy, and scanning electron microscopy, which reveal different features of the spores with different degrees of clarity. Our analyses show that CT can provide excellent detail on the three-dimensional structure of Mazon Creek plant fossils, with the nature of associated mineralization sometimes enhancing and sometimes obscuring critical information. Results provide guidance for selecting and prioritizing fossil plant specimens preserved in siderite concretions for future research.